The fireman : a novel - Hill, Joe (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2016)
No one knows exactly when it began or where it originated. A terrifying new plague is spreading like wildfire across the country, striking cities one by one: Boston, Detroit, Seattle. The doctors call it Draco Incendia Trychophyton. To everyone else its Dragonscale, a highly contagious, deadly spore that marks its hosts with beautiful black and gold marks across their bodiesbefore causing them to burst into flames. Millions are infected; blazes erupt everywhere. There is no antidote. No one is safe.
Keywords: Epidemics -- Fiction; Viruses -- Fiction; Horror fiction